Hidden diagnosis behind viral infection: the danger of anchoring bias - Iwai, Kenji (BMJ Case Rep, 2018)
Anchoring bias is one of the most common diagnostic biases that may lead to closed-minded thinking and could result in unnecessary tests, inappropriate patient management and even misdiagnosis. A 4-year-old boy was brought to the emergency department because of shaking chills. On the basis of bilateral swollen preauricular areas, high level of serum amylase and the prevalence of mumps, he initially received a diagnosis of mumps in spite of the shaking chills. However, blood culture turned out to be positive for two different kinds of bacteria. The patient finally received a diagnosis of polymicrobial bacteraemia resulting from suppurative appendicitis. We must consider and rule out bacteraemia in the differential diagnosis for patients who present with shaking chills, even in the presence of symptoms or information consistent with a more common viral infection such as mumps. In addition, intra-abdominal infection should be ruled out in the presence of polymicrobial enterobacteriaceae bacteraemia.